1995
DOI: 10.1063/1.115450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high temperature thermal stabilities of Ru and RuO2 Schottky contacts to GaAs

Abstract: Investigation of reactively sputtered tungsten nitride as high temperature stable Schottky contacts to GaAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…However, not too many conducting metal nitrides exist that meet the 5eV workfunction requirement. Many conducting metal oxides, on the other hand, have workfunctions near 5eV [3]. Thin films of transition metal oxides such as ruthenium oxide, RuO , and iridium oxide, IrO , not only have large workfunctions ( 5 eV), but also very low resistivity and excellent thermal/chemical stability [4]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, not too many conducting metal nitrides exist that meet the 5eV workfunction requirement. Many conducting metal oxides, on the other hand, have workfunctions near 5eV [3]. Thin films of transition metal oxides such as ruthenium oxide, RuO , and iridium oxide, IrO , not only have large workfunctions ( 5 eV), but also very low resistivity and excellent thermal/chemical stability [4]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Furthermore, because of excellent thermal stability, RuO 2 has also been proposed to serve as a potential electrode on GaAs and SiC for high temperature Schottky contact devices. 9,10 As an alternative gate electrode for integration with high-ZrO 2 and Zr silicate dielectrics in PMOS devices, excellent stability and electric properties indicated that RuO 2 is a promising candidate for implementation in PMOS devices. 11,12 However, detailed information on the work function of conductive oxides relating to the oxidation state is very limited.…”
mentioning
confidence: 99%
“…9,10 The work function of IrO x ͑Ͼ5.0 eV͒ is higher than that of ITO ͑ϳ4.7 eV͒. 11 Thus, it is expected that the interfacial layer of IrO x between ITO anodes and organic materials could improve the injection of holes via enhanced OLED electrical properties.…”
mentioning
confidence: 99%